Psychological well-being and its associated factors among university students in Sichuan, China - Wan, Juan; Wee, Lei Hum; Siau, Ching Sin; Wong, Yin How (Frontiers in Psychology, 2025)
IntroductionPsychological well-being refers to a mental state that allows an individual to achieve their full potential, be productive and innovative in their work, and manage everyday stressors. This study aims to assess university students’ psychological well-being by examining its associations with demographic factors such as gender, only child status, family background, grade level, financial aid status, and household income.MethodsThis cross-sectional, online study utilized the EPOCH Measure of Adolescent Well-being to examine five positive well-being indicators: Engagement, Perseverance, Optimism, Connectedness and Happiness among Chinese university students aged 18–25 years (N = 4,911).ResultsThe results showed that females, only children, first-year students, and urban students exhibited higher levels of psychological well-being. Additionally, students who received the highest level of financial assistance were significantly associated with lower levels of psychological well-being.ConclusionIdentifying the influence of these socioeconomic factors on psychological well-being allows for targeted interventions to improve the mental health and social well-being of at-risk groups.